How Groups Co-ordinate their Concepts and Terminology: Implications for Medical Informatics - Garrod, S. (Methods of Information in Medicine, 1998)
Conceptual and terminological systems are established and maintained by the communities who use them. This paper reports experiments which investigate the role of communication and interaction in the process. The experiments show that isolated pairs of communicators and virtual communities of interacting pairs naturally converge on their own conceptual and terminological systems when confronted with a common task. The results also indicate that the system converged on is optimal for that particular group engaged in that particular task. These findings are discussed in relation to the increasing use of tightly coordinated medical teams and its implications for getting them to adopt standardized medical terminologies.
Keywords: Concepts; Medical Terminology; Communication